PRABOWO SUBIANTO'S EUPHEMISM USED IN THE 2024 PRESIDENTIAL ELECTION DEBATE - Firdausi, Muhammad Anwar; Abdul Ghani, Mohamad Zulkifli; Rosyidah, Inayatur; Maghfur, Taa'ib; Kirom, Makhiulil (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
Prabowo Subianto is one of the 2024 presidential candidates participating in the Indonesian presidential election debate organized by the General Elections Commission (KPU). This debate features polite and non-offensive language, reflecting the use of euphemisms. This research aims to uncover the hidden practices in the use of euphemisms that Prabowo Subianto applied during the debate. A descriptive qualitative approach was employed, with the data consisting of orthographic transcriptions of his utterances. The data were collected through the observation method, advanced note-taking techniques, and documentation. The analysis was conducted using Content Analysis with Krippendorff's framework, which includes sampling, recording, and context units. The findings reveal ten types of euphemisms used by Prabowo Subianto, with loanwords being the most dominant, followed by hedges, overstatements, litotes, periphrasis, metaphors, downtoners, underspecification, apologetic expressions, and understatements. The study also identified eight main functions of euphemisms, and the most dominant function is being self-promotion, followed by protecting uncertain statements, as well as reducing hostility. This research enriches linguistic studies, particularly in the field of pragmatics, by demonstrating how various types of euphemisms are used in political communication.